130/80 mmHg as a unifying hypertension threshold for office brachial, office central, and ambulatory daytime brachial blood pressure. Issue 3 (7th February 2023) - Chuang, Shao‐Yuan; Cheng, Hao‐Min; Chang, Wei‐Lun; Yeh, Wan‐Yu; Huang, Chi‐Jung; Chen, Chen‐Huan
Abstract: The present study investigated the prognostic values for office brachial (OB), office central (OC), and ambulatory daytime brachial (AmDB) hypertension, as defined by a unifying threshold of 130/80 mmHg, and the incremental value of either OC or AmDB hypertension to OB hypertension. A total of 1219 community residents without receiving anti‐hypertensive treatment (671 men and 548 women, aged ≥ 30 years old) from central Taiwan and Kinmen islands had OB, OC, and AmDB blood pressure measurements during a cardiovascular survey conducted in 1992–1993. OB hypertension, OC hypertension, and AmDB hypertension were all defined in retrospect at the threshold of 130/80 mmHg. They were followed up for nonfatal and fatal cardiovascular events until December 31, 2017, by linking the baseline database to the National Health Insurance Research dataset and the National Death Registry. During a follow‐up of 25 612.5 person‐years (Average event‐free time: 21.0 years), there were 368 fatal and nonfatal cardiovascular events. In multivariable analyses, OB hypertension, OC hypertension, and AmDB hypertension had similar hazard ratios for cardiovascular events [2.03, 95% confidence interval: 1.47‐2.80]; 1.92 (1.47‐2.51); and 1.79 (1.41‐2.29), respectively. Using OB normotension as the reference, either the concordant OB and OC hypertension [2.24 (1.61‐3.12)], or the concordant OB and AmDB hypertension [2.52 (1.80‐3.54)] was significantly associated with cardiovascular events. Moreover, OB hypertension plus AmDB normotension was also significantly associated with increased risk for cardiovascular events. We concluded that OB hypertension, OC hypertension, and AmDB hypertension defined by a unifying threshold of 130/80 mmHg may provide similar estimates of long‐term risk for cardiovascular events. Cross‐classification analyses suggest that addition of OC hypertension or AmDB hypertension may improve the prognostic value of OB hypertension.